62. Efficacy of cathodal transcranial direct current stimulation in drug-resistant epilepsy: A proof of principle. Issue 12 (December 2016) - Assenza, G.; Campana, C.; Assenza, F.; Di Pino, G.; Fabrizio, E.; Fini, R.; Musumeci, G.; Tombini, M.; Di Lazzaro, V.
Abstract : It has been proved that Transcranial DCS (tDCS) can modulate cortical excitability, enhancing or decreasing, respectively by anodal or cathodal polarity. The short-term and lasting alterations induced by tDCS are strictly related to the charge density, duration of stimulation and the depth of neuron below the skull. Epilepsy represents a pathophysiological model of unbalanced relation between cortical excitation and inhibition. In this line, tDCS can be exploited to counterbalance the neuronal hyper-excitation through electric neural modulation. This paper aims at providing the efficacy of cathodal tDCS in reducing seizures' frequency in drug-resistant focal epilepsy. The study was single blind and sham-controlled and compared seizure rate in the 7 days before and after tDCS and after sham in a cross-over design. 9 patients affected by focal resistant epilepsy were enrolled. After tDCS 3 out 9 patients have not any change in seizure rate. 6 patients reduced their seizure frequency >50%. No significant modification were recorded after sham. This study represents the proof that cathodal tDCS may be efficient in reducing seizures'frequency in focal resistant epilepsy.